CHOICE OF OPMIMUM MATERIAL FOR STRENGTHENING THE ENTRANCE EDGES OF STEAM TURBINE ROTOR BLADES - Gluschcova, D.; Grinchenko, E.; Voronova, Ye.; Глушкова, Д. Б.; Гринченко, Е. Д.; Воронова, Е. М.; Глушкова, Д. Б.; Грінченко, О. Д.; Воронова, Є. М. (Харьковский национальный автомобильно-дорожный университет, 2016)
The influence of electrode material on the state of surfacing layer of steam turbine rotor blades is researched. The strengthened layer was produced by electro-spark alloying, using alloy T15K6 and steel 15X11МФШ. The microstructure, microhardness and thickness of surfacing layers were investigated. The advantages of steel 15X11МФШ for strengthening the entrance edges of steam turbine rotor blades which makes it possible to simultaneously harden both the entrance edges of rotor blades as well as increase their erosive resistance are grounded.
ВЫБОР ОПТИМАЛЬНОГО МАТЕРИАЛА ДЛЯ УПРОЧНЕНИЯ ВХОДНЫХ КРОМОК РАБОЧИХ ЛОПАТОК ПАРОВЫХ ТУРБИН
ВИБІР ОПТИМАЛЬНОГО МАТЕРІАЛУ ДЛЯ ЗМІЦНЕННЯ ВХІДНИХ КРАЙОК РОБОЧИХ ЛОПАТОК ПАРОВИХ ТУРБІН
Keywords: electro-spark alloying; electrode; surfacing layer; microstructure; microhardness; strengthening; электроискровое легирование; электрод; наплавленный слой; микроструктура; микротвердость; упрочнение; електроіскрове легування; електрод; наплавлений шар; мікроструктура; мікротвердість; зміцнення; 624.21